Computer-assisted vacuum aspiration mechanical thrombectomy with Lightning Flash allows broader clinical application, enhanced procedural safety, and improved clinical outcomes for the treatment of acute and subacute iliofemoral and central deep venous thrombosis - Taimur Saleem, MD, FACS; Seshadri Raju, MD, FACS (Journal of Vascular Surgery Cases and Innovative Techniques)
We describe our experience with the 16F Lightning Flash vacuum aspiration mechanical thrombectomy system in 25 patients. All patients were treated in a single session with a mean estimated blood loss of 60 mL. Alteplase was not used in any patient in this series. Resolution of at least 50% thrombus or more at the end of the procedure on intravascular ultrasound examination was performed for all patients. Eight-eight percent of patients maintained venous patency at their most recent follow-up range, 8-26 months). No perioperative pulmonary embolism or device-related complications were observed.